Counter-propagating streamers in an atmospheric-pressure helium plasma jet. (21st April 2017) - Hasan, M I; Cvelbar, U; Bradley, J W; Walsh, J L
Abstract: This study explores an atmospheric pressure plasma jet impinging on a downstream dielectric surface using a 2D numerical plasma fluid model. It is demonstrated that a counter-propagating discharge ignites at the exposed dielectric surface when the discharge is ignited using negative polarity voltage pulses with fall times in the microsecond range. Two distinct streamer discharges are created, a cathode-directed streamer propagating upstream toward the cathode, and an anode-directed streamer propagating parallel to the dielectric surface facing the gas flow. The surface discharge propagating parallel to the dielectric surface deposits negative surface charge. It is also shown that driving an APPJ with a negative applied potential significantly increases the O 2 − time-averaged flux to the dielectric surface while decreasing the O 2 + time-averaged flux.